Recurrent gene mutations detected in canine mast cell tumours by next generation sequencing - Vozdova, Miluse; Kubickova, Svatava; Pal, Karol; Fröhlich, Jan; Fictum, Petr; Rubes, Jiri (Veterinary and comparative oncology, 2020)
Genetic causes of canine mast cell tumours (MCTs), except for mutations in the KIT gene detected in some MCTs, are generally unknown. We used whole exome sequencing to reveal mutation spectra in canine MCTs. We detected somatic mutations in 87 genes including 10 genes recognized as human cancer drivers. Besides KIT, 14 other genes were recurrently mutated. Subsequently, we performed next generation sequencing of a panel of 50 selected genes in additional MCT samples. In this group, the most frequently altered gene was GNB1 showing a recurrent dinucleotide substitution at position of Gly116 in 30% of the MCT samples (n = 6/20) and Ile80 substitution accompanied by a splice region mutation in one case. We extended the study by analysis of the above mentioned GNB1 regions in additional MCT samples by Sanger sequencing, and assessed the overall prevalence of GNB1 mutations to 17.3% (n = 14/81), which is similar to the prevalence of KIT alterations. Our results indicate that GNB1 mutations are probably involved in canine MCT pathogenesis in both cutaneous and subcutaneous MCT cases. As opposed to KIT alterations, the presence of GNB1 mutations did not negatively affect survival times, and our data even showed a trend towards positive prognosis. If our results are confirmed in a larger number of MCTs, an extension of molecular testing of canine MCTs by GNB1 analysis would help to refine the molecular stratification of MCTs, and become useful for targeted treatment strategies.
Keywords: mastocytární sarkom; vysoce účinné nukleotidové sekvenování; psi; mastocyty; mutace; Dog Diseases; High-Throughput Nucleotide Sequencing; Mast Cells; Animals; Mutation; Dogs; Proto-Oncogene Proteins c-kit; nemoci psů; zvířata; Mast-Cell Sarcoma; protoonkogenní proteiny c-kit; GTP-Binding Protein beta Subunits; proteiny vázající GTP - beta-podjednotky